Energetics of swimming with hand paddles of different surface areas - Crocker, G. H.; Moon, J. F.; Nessler, J. A.; Newcomer, S. C. (The Journal of Strength and Conditioning Research, 2021)
Hand paddles are one of the most common training aids used by the competitive swimmer, yet little is known regarding how hand paddle surface area affects the metabolic cost of transport (COT) while swimming. The purpose of this study was to determine how altering hand paddle size affects energy use during submaximal, front-crawl (i.e., freestyle) swimming. Twenty-six proficient, adult swimmers (13 men and 13 women) completed six 3-minute trials in a flume at a constant pace (102 cm/s; 1:38 per 100 m). Trials were performed in random order, using 1 of 5 pairs of hand paddles of different sizes or no paddles at all. Paddle surface areas were 201, 256, 310, 358, and 391 cm2 per hand. Without paddles, COT, arm cadence, and distance per stroke were 7.87 ± 1.32 J/kg/m, 29.4 ± 4.9 min-1, and 2.13 ± 0.34 m, which corresponded to a rate of oxygen consumption (Vo2) of 23.3 ± 3.7 ml/kg/min and a heart rate (HR) of 118 ± 17 b/min. The use of larger hand paddles decreased COT, cadence, Vo2, and HR and increased distance traveled per stroke (all p < 0.001). However, the magnitude of the change of COT decreased as paddle size increased, indicating diminishing marginal return with increasing paddle surface area. The largest sized paddles increased COT per stroke compared with swimming without paddles (p = 0.001). Therefore, results from this study suggest that an optimal hand paddle size exists (210-358 cm2) for proficient, adult swimmers, which reduces COT without increasing COT per stroke.